The growth-at-risk perspective on the system-wide impact of Basel III finalisation in the euro area - Katarzyna Budnik; Ivan Dimitrov; Carla Giglio; Johannes Groß; Max Lampe; Andrei Sarychev; Matthieu Tarbé; Gianluca Vagliano; Matjaz Volk (European Central Bank (ECB), 2021)
This paper assesses the macroeconomic implications of the Basel III finalisation for the euro area, employing a large-scale semi-structural model encompassing over 90 banks and 19-euro area economies. The new regulatory framework will influence banks' reactions to economic conditions and, as a result, affect the ability of the banking system to amplify or dampen economic shocks. The assessment covers the entire distribution of conditional economic predictions to measure the cost and benefit of the reforms. Looking at the means of conditional forecasts of output growth provides an indication of the costs of the reform, namely a transitory reduction in euro area gross domestic product (GDP) and in lending to the non-financial private sector. Looking at the lower percentile of output growth forecasts, i.e. growth at risk, captures the long-term benefits of the Basel III finalisation package in terms of improved resilience and the ability of the banking system to supply lending to the real economy under adverse conditions. These permanent growth-at-risk benefits ultimately outweigh the short-term costs of the reform.
Keywords: E37; E58; G21; G28; 330; Basel III finalisation; impact assessment; regulatory policy; bankingsector; real-financial feedback mechanism